Answer:
12¾
Step-by-step explanation:
x - ¾ = 12
x = 12 + ¾
c = 12¾ or 12.75
−<span>3<span>(<span><span>4a</span>−<span>5b</span></span>)</span></span><span>=<span><span>(<span>−3</span>)</span><span>(<span><span>4a</span>+<span>−<span>5b</span></span></span>)</span></span></span><span>=<span><span><span>(<span>−3</span>)</span><span>(<span>4a</span>)</span></span>+<span><span>(<span>−3</span>)</span><span>(<span>−<span>5b</span></span>)</span></span></span></span><span>=<span><span>−<span>12a</span></span>+<span>15<span>b</span></span></span></span>
Answer:
1320
Step-by-step explanation:
880/8 = 110
12x110 = 1320
Answer:
Using the right angles, we can establish AAS making the triangles congruent. Or using the Pythagorean Theorem, we can find the missing side, and then use SSS, SAS, or ASA to make the triangles congruent.
Step-by-step explanation: